Investigating The Impact of Awareness and Readiness on Security Concerns in Cloud Computing Adoption Among Malaysian Diploma of Information Technology Students at Polytechnic Sultan Mizan Zainal Abidin - Razak , Norhayati Saa’dah Che Abd; Awang , Nor Syahadataini (Tropical Scientific Journal, 2026)
Objective: This study investigates the relationship between students’ awareness, readiness, and security concerns in the adoption of cloud computing technologies among Diploma in Information Technology students at Polytechnic Sultan Mizan Zainal Abidin. It aims to explore how students’ levels of awareness and readiness influence their perceptions of privacy and data security when using cloud-based platforms in academic settings. Research Method: A quantitative research method was applied using a structured questionnaire distributed to 254 students chosen through simple random sampling. The questionnaire measured three core construct awareness, readiness, and security concerns in relation to cloud computing. Data analysis was carried out using descriptive statistics and Pearson correlation with the aid of Microsoft Excel. Findings: The results indicated high mean scores for awareness (M = 4.04, SD = 0.81), readiness (M = 4.00, SD = 0.81), and security concerns (M = 4.01, SD = 0.82). Correlation results demonstrated a moderate positive relationship between readiness and security concerns (r = 0.577, p < 0.05), as well as between awareness and security concerns (r = 0.573, p < 0.05). These findings suggest that students with higher awareness and readiness levels are more attentive to issues involving data protection and cybersecurity. Originality: The findings of this study contribute to the limited research addressing how awareness, readiness, and security concerns interact in the context of cloud computing adoption among Malaysian diploma-level students in Information Technology. Drawing from a polytechnic environment, the study delivers new empirical perspectives on a segment of upcoming IT professionals that have received relatively little attention.